2019
DOI: 10.1097/iop.0000000000001406
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Orbital Decompression by Oculoplastic Surgeons for Proptosis in Thyroid Eye Disease

Abstract: The authors report the outcomes of a series of endonasal orbital decompression carried out by oculoplastic surgeons. Purpose: Orbital decompression is an established surgical treatment option for a range of orbital conditions. Traditionally, Ear, Nose and Throat surgeons have adopted the endoscopic route while ophthalmologists operate via an external approach. The authors report the outcomes of endonasal decompression performed by oculoplastic surgeons experienced in endonasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[26][27][28] Nowadays, to reduce the lateral wall decompression has noticeably attracted scholars' attention because of the low occurrence rate of postoperative diplopia and strabismus. [29] In Valerie et al's study, the removal of the medial and inferior walls provided a proptosis reduction of 3.9 mm, while the three-wall decompression reduced proptosis by 7.6 mm, [30] indicating that the removal of lateral wall had a great in uence on the value of proptosis reduction. In the present study, 16 of 22 patients in the transconjunctival group and 21 of 24 patients in the transnasal group experienced the removal of lateral wall (P = 0.276).…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Nowadays, to reduce the lateral wall decompression has noticeably attracted scholars' attention because of the low occurrence rate of postoperative diplopia and strabismus. [29] In Valerie et al's study, the removal of the medial and inferior walls provided a proptosis reduction of 3.9 mm, while the three-wall decompression reduced proptosis by 7.6 mm, [30] indicating that the removal of lateral wall had a great in uence on the value of proptosis reduction. In the present study, 16 of 22 patients in the transconjunctival group and 21 of 24 patients in the transnasal group experienced the removal of lateral wall (P = 0.276).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Results are variable and the case series by Juniat (2019) and Woods (2019) have shown that a mean reduction of 3.3 mm or more is possible with endoscopic two-wall orbital decompression. [15][16][17] The smaller reduction in the current study may be due to the low preoperative proptosis. In this study, the mean preoperative proptosis was 19.82 ± 2.84 mm, smaller than that in the previous studies.…”
Section: Discussionmentioning
confidence: 99%